The Uniqueness of Islamic Culture - YILMAZ, Sinan (Journal of History Culture and Art Research, 2014)
The Uniqueness of Islamic Culture Abstract This paper examines the main reasons behind why Islamic culture is different than other cultures. In the introduction part of the paper, the usage area of the words culture and civilization were tackled. In the first part of the paper, an evaluation of the uniqueness of Islamic culture was made and examples about this were given. In the second part of the paper, evaluations about how Islamic culture has struggled with modernization and secularization and how it has shaped itself as a result of this were made. In the third part of the paper, the situation in which Islamic civilization has regressed against the Western civilization causing emerging arguments and the current situation in Islamic civilization have been addressed by making evaluations on culture and civilization. In the final part, evaluations on thesis this paper has used were made.